Susceptibility to propoxur in populations of Aedes aegypti (Diptera: Culicidae) in the department of Córdoba, Colombia - Jaramillo-González, Lilian Yovana; Montes-Castro, Darlinson; Atencia-Pineda, María Claudia; Hoyos-López, Richard; Calderón-Rangel, Alfonso; Díaz-Ortíz, Diana; Pareja-Loaiza, Paula; García-Leal, Javier; Flores, Adriana E.; Maestre Serrano, Ronald (Revista Colombiana de Entomología, 2025)
In Colombia, the increased use of pyrethroids and organophosphates in response to rising dengue cases and the emergence of chikungunya and Zika has led to the development of resistance in Aedes aegypti. This highlights the need to explore the effectiveness of other insecticides against Ae. aegypti and the diseases it transmits. In this context, we assessed the susceptibility of 15 Ae. aegypti populations from Córdoba, Colombia, to propoxur, a carbamate insecticide. Susceptibility was evaluated using a standardized bottle assay with a diagnostic dose (DD) of 12.5 μg/bottle and a diagnostic time (DT) of 30 minutes, as recommended by the Centers for Disease Control and Prevention (CDC). The results showed that the evaluated populations were susceptible to propoxur, with 100 % mortality. This finding underscores the potential of propoxur for managing Ae. aegypti in areas where there is resistance to traditional insecticides in the department of Córdoba.